Anxiety, depression, and comorbid symptomatology: different forms and severity of intimate partner violence perpetrated by men seeking help - Claing, Aurélie (Violence and victims, 2024)
Intimate partner violence (IPV) is a serious public health issue associated with numerous deleterious outcomes. Previous studies highlighted the relevance of documenting psychological predictors of IPV to identify prevention strategies. This study examined the links between anxious and depressive symptomatology and perpetrated physical, psychological, and sexual violence among 494 French-Canadian men seeking help for IPV-related difficulties. Differences in the frequency of perpetrated IPV were examined across four groups: (a) no anxious or depressive symptoms reaching a cutoff of high distress, (b) symptoms of anxiety, (c) symptoms of depression, and (d) comorbid symptoms. Results highlighted that men with comorbid symptoms perpetrated significantly more severe violent acts compared to the other groups. This study underscores the importance of targeting the reduction of psychological distress when treating men who perpetrated IPV.